Rare use of twin Solitaire (R) stents in the double waffle-cone technique for endovascular treatment of a wide-necked bifurcation aneurysm - KAYA, AHMET; Nas, Omer Fatih; Kacar, Emre; Kaya, AHMET; Erdogan, Cuneyt; Hakyemez, Bahattin (My University, 2015)
Endovascular treatment of wide-necked bifurcation aneurysms may be challenging. The waffle-cone technique can be used in these aneurysms in case of acute angulation between parent artery and distal artery of the aneurysm. Solitaire (R) stent (Ev3, Irvine, CA, USA) has the significant advantage of mitigating the potential complication risks. This study reports the second case in the literature in which endovascular treatment of a wide-necked bifurcation aneurysm with the double waffle-cone technique by using twin Solitaire (R) stents proved to be successful.